Storytelling across cultures: engendering literacy the 'papa Rudy' way (2010)
This article examines the approches to storytelling as a means of encouraging literacy employed by professor Rudy Wilson across cultures of the United States and Nigeria. It discusses the opportunities storytelling provides for children to develop an interest in reading and to build language skills. A report on an interview with Professor Wilson (known as 'papa Rudy' in Nigeria is supplemented by observations of his storytelling activities in Nigeria. The researches conclude that storytelling is a vaible tool for teaching and reading. Findings show that children across cultures love stories, but thier level of concerntration varies with the number of alternative activities to which the child is exposed. More importantly, the success of the storytelling session depends on the teacher's creative ability and flexibility